The Quality of Foreign Aid: Country Selectivity or Donors Incentives? - Wane, Waly (World Bank, Washington, D.C., 2013)
The author investigates the determinants of foreign aid quality. He shows that design effects are a crucial component of quality. He thus establishes that donors have an impact on the quality of the foreign assistance they provide. The author also shows both theoretically and empirically that the quality of aid is endogenous to the relationship between the donor agency and the recipient government. Highly capable and accountable governments accept only well-designed projects, whereas governments with low accountability may accept poor quality projects either because they are unable to assess the worth of the projects or they will benefit personally.